Models for Assessing the Impact of Family Planning on Fertility - Aryal, Roshan; Aryal, Tika Ram; Bhusal, M.K. (Journal of Institute of Science and Technology, 2015)
This paper tries to assess the impact of family planning (FP) on fertility in Nepal. Nepal Demographic and Health Survey data 2011 were used. Impact of sterilization was found to be highest (about 33 per cent births averted) followed by the combined effect of injectables, pills, condoms and all other traditional methods. The combined impact of sterilization and injectables was found to be 0.60 births per woman. The expected numbers of future children would be 3.09 (excluding sterilization), 3.27 (excluding sterilization or injectables), 3.36 (excluding sterilization or injectables or pills), 3.51 (excluding sterilization or injectables or pills or condoms) and 3.97 (non-user) for zero parity women. The combined impact of sterilization and injectables would be 0.60 births per woman. Findings may help researchers and policy-makers for designing effective FP policy of a country. Journal of Institute of Science and Technology, 2015, 20(2): 67-72